Computational Fluid Dynamics (CFD) Modelling of Annular Reactor for Photocatalytic Degradation of Air Pollutants Using COMSOL Multiphysics Software - Goran Sabol; Benjamin Radetić; Ivana Grčić; Sanja Kalambura; Darko Kiš (Tehnički Vjesnik)
An annular reactor is a type of reactor in which chemical reactants move through an annular gap between two concentric cylinders. This type of design is suitable for a variety of chemical processes because it facilitates efficient heat transfer and mixing of reactants. Previous research has shown that this type of reactor shows promising results in the photocatalytic decomposition of pollutants, which is why it is used in air purification tests. This paper presents a model of one such type of air purification reactor modeled in COMSOL Multiphysics simulation software and provides an overview of the steps that need to be taken in order to effectively model the photocatalytic oxidation. The purpose of modelling the reactor is to test its effectiveness in computer simulations of the decomposition of pollutants in the air using the process of photocatalytic oxidation, which is a combination of photooxidation based on the effect of UV radiation and catalytic oxidation. The resulting simulations allow the scaling of the system (its increase or decrease) so that it can be adapted to certain conditions and used in the real world as a method of air purification at the very sources of polluted air.